A Rare Presentation of Primary Intracranial Malignant Melanoma: Case Report and Review of Literature - Jigna Patel; Rutik Thorat; Trupti Jansari (Medical Research and Its Applications Vol. 4, 2024)
This case provides us with a good learning opportunity, which is to increase recognition and awareness of rare entity of primary malignant melanoma. Melanocytes or melanoblasts, the precursor cells of melanocytes, are the source of malignant melanoma. It is not surprising that primary melanomas can develop within the central nervous system because melanocytes are present in normal leptomeningeal tissue. Primary melanocytic tumors of the central nervous system (CNS) form a rare entity which is histologically and clinically distinct from metastatic cutaneous or retinal malignant melanoma. It is difficult to diagnose a primary CNS melanoma upfront. Here, we are presenting a rare case of primary malignant melanoma in left frontoparietal area in 65 years old male patient. This case provides us with a good learning opportunity, which is to increase recognition and awareness of rare entity of primary malignant melanoma. Options are limited for the treatment of Malignant Melanoma of the brain. Standard treatment models include surgical resection of the tumor, whole brain radiotherapy, stereotactic radiosurgery and chemotherapy.